2019
DOI: 10.1016/j.jhlste.2019.100202
|View full text |Cite
|
Sign up to set email alerts
|

Using student data: Student-staff collaborative development of compassionate pedagogic interventions based on learning analytics and mentoring

Abstract: UK Universities are increasingly being 'encouraged' to focus on student engagement, retention and performance, with learning analytics becoming commonplace. Based on inter-related student-staff partnerships, this study adopted a human and compassionate approach to the use of student data and subsequent interventions. Analysis of focus group and interview data from 86 student participants explored key themes: peer-mentoring increasing engagement with the communal-habitus; increased confidence and engagement; an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…For instance, Wang and Zhu ( 2019 ) observed that the use of digital technologies in teaching is capable of supporting high-quality and transformed educational process by comparing the performances/outcomes of the learners in a MOOC-based, flipped classroom, and traditional class settings, respectively. Whereas, the study by Abu Zohair ( 2019 ) that used the machine learning techniques to analyze educational datasets, shows that adequate (accurate) prediction of students’ data or analysis may have not only been crucial in improving the students' performance/experiences (Benkwitz et al, 2019 ; Crues et al, 2018 ; Kori et al, 2018 ; Weston et al, 2019 ), but also represents as a useful tool towards the promotion of the various university’s ranking or status (Medne et al, 2020 ; Mourad, 2017 ; Tóth & Surman, 2019 ).…”
Section: Background Informationmentioning
confidence: 99%
“…For instance, Wang and Zhu ( 2019 ) observed that the use of digital technologies in teaching is capable of supporting high-quality and transformed educational process by comparing the performances/outcomes of the learners in a MOOC-based, flipped classroom, and traditional class settings, respectively. Whereas, the study by Abu Zohair ( 2019 ) that used the machine learning techniques to analyze educational datasets, shows that adequate (accurate) prediction of students’ data or analysis may have not only been crucial in improving the students' performance/experiences (Benkwitz et al, 2019 ; Crues et al, 2018 ; Kori et al, 2018 ; Weston et al, 2019 ), but also represents as a useful tool towards the promotion of the various university’s ranking or status (Medne et al, 2020 ; Mourad, 2017 ; Tóth & Surman, 2019 ).…”
Section: Background Informationmentioning
confidence: 99%
“…Prediction has been one of the most attractive fields of EDM since 1995 [3]. Related studies usually exploit potential factors from the university's data [4] to build a prediction model such as GPA or student's performance. Various Machine Learning algorithms are used to solve these problems including Decision Tree, Random Forest, Regression, and Neural Network [9,34,42].…”
Section: Introductionmentioning
confidence: 99%